Correlation Analysis of the Entorhinal Cortex-Hippocampus Nerve Fiber Changes and Memory Dysfunction in P301L-Tau Mouse Model and Molecular Mechanism - CHEN Xiaocheng; LIANG Shengxiang; LIN Bingbing; LIU Weilin; HUANG Jia (康复学报)
ObjectiveTo observe the correlation between the changes of entorhinal cortex-hippocampus nerve fibers and learning and memory function in the P301L-Tau mouse model of Alzheimer's disease (AD) and related molecular mechanism, so as to provide the evidence for Tau-targeted treatment in AD patients.MethodsA total of 16 3-month-old male C57BL/6 mice were randomly divided into non-vector virus control group (control group) and P301L-Tau model group (model group), with eight mice in each group. After anesthesia, non-vector virus was injected into the bilateral entorhinal cortex of mice in the control group, and AAV-P301L-Tau virus was injected into the bilateral entorhinal cortex of mice in the model group. After the injection, they were routinely fed to 12 months of age. Morris water maze test was used to detect the learning and memory function. Diffusion tensor imaging (DTI) scanning was used to detect the changes of nerve fibers in the bilateral entorhinal cortex and hippocampus. Western blot was used to detect the expression levels of t-Tau, p-Tau (Ser262), and glycogen synthase kinase-3β (GSK3β). Pearson correlation analysis was used to analyze the correlation between fractional anisotropy (FA) values in different brain regions of the entorhinal cortex-hippocampus and their corresponding learning and memory functions.Results(1) Learning and memory function test: compared with the control group, the learning and memory function of the model group significantly decreased, the escape latency significantly increased, the number of platform crossings and time ratio of target quadrant significantly decreased (P<0.05). (2) Structure of nerve fibers in the entorhinal cortex and hippocampus: compared with the control group, FA values of the entorhinal cortex and hippocampus in the model group decreased more significantly, MD values of the entorhinal cortex in the model group increased more significantly, while there was no significant difference in the MD values of the hippocampus in the model group (P>0.05). (3) Correlation analysis between FA values in the entorhinal cortex-hippocampus and learning and memory function: FA values in the entorhinal cortex and hippocampus were positively correlated with the number of platform crossings (r=0.76, P<0.05; r=0.62, P<0.05). (4) Expression of t-Tau, Ser262 and GSK3β protein in the entorhinal cortex-hippocampus: compared with the control group, the expression of t-Tau, p-Tau (Ser262) and GSK3β protein of entorhinal cortex and hippocamp increased more significantly in the model group (P<0.05).ConclusionThe Tau protein in the entorhinal cortex-hippocampus of the P301LTau mouse model was hyperphosphorylated, which leads to destruction of the nerve fiber structures in the entorhinal cortex-hippocampus and learning and memory dysfunctions. The degree of learning and memory dysfunction was positively correlated with the nerve fiber damage of entorhinal cortex and hippocampus.